The genus Dromanthomorphus Pic, 1921 (Coleoptera, Cleroidea: Malachiidae) in South-East Asia - Tshernyshev, Sergei E. (Zootaxa, 2016)
South-East Asian species of the genus Dromanthomorphus Pic, 1921 and several species provisionally attributed to Hadrocnemus Kraatz, 1895 are studied, and their taxonomic position is specified. Three new species are described from the Philippines: D. subflabellatus Tshernyshev, sp. n., D. restrictus Tshernyshev, sp. n. and D. subtilis Tshernyshev, sp. n. Seven species are transferred from Hadrocnemus to Dromanthomorphus, D. apoensis (Wittmer, 1999) comb. n., D. blaisei (Pic, 1926) comb. n., D. chiangensis (Wittmer, 1999) comb. n., D. depressicornis (Pic, 1919) comb. n., D. gravieri (Pic, 1923) comb. n., D. javanus (Wittmer, 1989) comb. n. and D. tonkineus (Pic, 1919) comb. n. Three species are transferred from Dromanthomorphus to Oculapalochrus Tshernyshev, 2015, O. ranuensis Wittmer 1990 comb. n., O. saigonensis (Pic, 1951) comb. n. and O. suttoni Wittmer, 1995 comb. n., and two species from Dromanthomorphus to Mimapalochrus Tshernyshev, 2015, M. cingalensis (Champion, 1921) comb. n. and M. dolokensis Wittmer, 1999 comb. n. Illustrations of male external appearance, metathoracic appendage, urites and genitalia, and distribution maps are provided. A determination key to all species of Dromanthomorphus from South-East Asia is also proposed.